Osnovni tendencii v užyvanni čyslivnykiv v ukrains'kij movnij praktyci XXI storiččja - Kolibaba, Larysa (Slavistična revija, 2025)
The article pr?sents a comprehensive analysis of the main trends in the use of numerals in Ukrainian language practice during the first quarter of the 21st century. The trends are divided into two categories: 1) positive and 2) negative. Positive trends include the increased use of forms with the endings -?? and -?? in oblique cases of proper cardinal numerals; the expanded compatibility of collective numerals with nouns of all genders; and the replacement of prepositional forms of the local case with numerals in the form of the genitive case without a preposition in temporal constructions. Negative trends include the agreement of the numerals two, three, four in the nominative plural with masculine nouns of the 2nd declension on -? (-?); the use of quantitative numerals with the foreign component top-; the incorrect naming of calendar years; and the violation of the norms of declining numerals – names of hundreds. The article attempts to assess these changes in the use of numerals in terms of their conformity to the historically established grammatical features of the Ukrainian literary language and their practical relevance.
Keywords: 21. st.; 21st century; jezikovna raba; modern Ukrainian language usage; numerals; števnik; trendi; trends; Ukrainian language; ukrajinščina